Morbility in the students of the Polytechnic State University of Carchi, related to lifestyles. (Horizontes de Enfermería, 2018)
This research aims to identify the morbidity and life styles related to the State Polytechnic University of Carchi (UPEC) students"™ heath, during the period February " August 2017, based on the university stage, which represents a moment of change of lifestyle and adaptation; it also demands to take decisions, propose goals, recognize oneself and take responsibilities, especially about health. That is why on the forming of the required person; the young students need the tools that allow them to keep their health and enjoy a better lifestyle. A quantitative, descriptive, transversal and correlational study was carried out; it was addressed to characterize the morbidity and its relation with UPEC students"™ lifestyle, using the virtual survey as the study technique in order to do the health diagnosis of the university community, and statistical data of the university medical center. The results obtained show that the predominant pathologies are those of the respiratory system in 44% according to statistical data of the medical center, and from the virtual survey 65% of the students, followed by 52% who affirmed to consume a diet based on carbohydrates, besides 41.9% of the women who said they did not do any physical activity, being this an issue of risk factor to develop not-transmitted chronic diseases, main cause of morbidity and mortality in our country, which generates in long time a high cost in health. In conclusion, it is essential to make student population aware about the importance of health care, the adoption of healthy habits contributes to their school performance and reduces morbidity and mortality due to these pathologies generate a high cost for the state.
Keywords: health; morbidity; risk factors; healthy habits